Intake of flavonoids from Astragalus membranaceus ameliorated brain impairment in diabetic mice via modulating brain-gut axis - Xuling Li; Tingting Zhao; Junling Gu; Zhe Wang; Jing Lin; Rushang Wang; Tingting Duan; Zhenghai Li; Ruixue Dong; Weiming Wang; Kin-Fong Hong; Zhilong Liu; et al. (BMC, 2022)
Abstract Background Brain impairment is one of a major complication of diabetes. Dietary flavonoids have been recommended to prevent brain damage. Astragalus membranaceus is a herbal medicine commonly used to relieve the complications of diabetes. Flavonoids is one of the major ingredients of Astragalus membranaceus, but its function and mechanism on diabetic encepholopathy is still unknown. Methods Type 2 diabetes mellitus (T2DM) model was induced by high fat diet and STZ in C57BL/6J mice, and BEnd.3 and HT22 cell lines were applied in the in vitro study. Quality of flavonoids was evaluated by LC-MS/MS. Differential expressed proteins in the hippocampus were evaluated by proteomics; influence of the flavonoids on composition of gut microbiota was analyzed by metagenomics. Mechanism of the flavonoids on diabetic encepholopathy was analyzed by Q-PCR, Western Blot, and multi-immunological methods et al. Results We found that flavonoids from Astragalus membranaceus (TFA) significantly ameliorated brain damage by modulating gut-microbiota-brain axis: TFA oral administration decreased fasting blood glucose and food intake, repaired blood brain barrier, protected hippocampus synaptic function; improved hippocampus mitochondrial biosynthesis and energy metabolism; and enriched the intestinal microbiome in high fat diet/STZ-induced diabetic mice. In the in vitro study, we found TFA increased viability of HT22 cells and preserved gut barrier integrity in CaCO2 monocellular layer, and PGC1α/AMPK pathway participated in this process. Conclusion Our findings demonstrated that flavonoids from Astragalus membranaceus ameliorated brain impairment, and its modulation on gut-brain axis plays a pivotal role. Our present study provided an alternative solution on preventing and treating diabetic cognition impairment.